Cloud Threat Detection: Big Data Based Security Analytics Approach - Padhye, Krishnavandan; Dwivedi, Shreya; S. Sharanya, (International Journal of Psychosocial Rehabilitation, 2020)
The cloud infrastructure consists of VMs (Virtual Machines) and hosting hardware which creates multiple instances of resources defined by the software. The VMs manage, support and monitor the software defined multi-instance framework. The potential of system to perform real time resource scaling has led to widespread implementation of virtualized infrastructure for cloud computing. This has caused virtual infrastructure to become a tempting target for cyber attackers to launch attacks and to gain illegal access. This paper analyses the threats posed by cyber criminals and the development of threat detection methods over time this gives us insight on what are the current requirements of security researchers to make the system more efficient and accurate to detect threats in real time. The paper also discusses about leveraging technologies like big data and machine learning which can handle huge amount unstructured data and are designed to run on a distributed network.